Evaluation Of Mitragyna Speciosa Korth. (Ketum) Extracts Prepared By Accelerated Solvent Extraction Technique, On Antinociceptive And Cytotoxicity Effects - Goh, Yong Sean (2021)
Mitragyna speciosa Korth. (Ketum) leaves are well known for their psychoactive and analgesic properties. Mitragynine, is the principal alkaloid of ketum leaf, is a well-known factor that contributes to ketum’s pharmacological activities. The present study underlined the use of green solvent and green extraction technique for the yield of a better and safe ketum extract. At first, ketum was extracted with pure water using conventional extractions, Soxhlet, and maceration, as well as modern extraction techniques, ultrasound-assisted extraction (UAE), and accelerated solvent extraction (ASE) techniques. Subsequently, two green extraction techniques which are ASE, and UAE were selected. Solvents such as water, methanol, ethanol, and ethyl acetate were used in the optimisation of ASE and UAE. Comparing both extractions, ASE demonstrated a better dry yield (0.53 – 2.91 g) with consistent mitragynine content (6.53 – 7.19 %), shorter time (5 minutes), and reduced solvent usage (< 100 mL).